Pandemics' Contagion And Spillover Effects On Global Financial Markets - Faurani Santi Singagerda; Anggalia Wibasuri; Andi Desfiandi (International Journal of Artificial Intelligence Research, 2022)
This study will examine at the relationships and influence of economy factors on another variable of the Covid-19 Pandemic effect on The Financial Market Index on The Indonesia Stock Exchange during the coronavirus pandemic. Considering daily Covid-19 confirmed cases from the United States and China, as well as the Stock Indexes of the United States, China, and Indonesia from January 1, 2020 to October 30, 2020. The results demonstrate that the total active instances of Covid-19 in the United States (USAC) have a positive impact on the Indonesian Financial Market Index (JKFINA). It is indicated by a decline in primary industry and its contribution to economic growth, which has impacted on China's raw material export to Indonesia. Many corporations have dropped, causing issues with the banking industry and, as a result, a negative influence on the Indonesian Financial Stock Index (JKFINA). Given these conditions, the Indonesian government must fully support the activities of small, medium, and large businesses in order to maintain and promote Indonesia's export activities, provide simplicity in export permits, accelerate the export licensing process, and pay more attention to the rules set by the US. Due to the restriction of raw material supply from China, Indonesia needs to be able to optimize its own resources